The Impact of Visitors and Domestic Waste on Water Quality and Fish Ecosystems in the Cirahab Water Source in Curuggoong Village, Padarincang District, Serang Regency, Banten - Hermawan Hermawan; Wulan Sari Handayani; Yeni Haerani (Transpublika Publisher, 2025)
Detergent is a product that has a function as a dirt remover on clothes when washing, detergent is thrown away excessively in the waters it will have a bad impact on aquatic biota, such as fish, aquatic plants, or organisms that live in water, besides that it will also reduce the O2 levels in the water, damage organs in fish and death in fish due to detergent pollution. The more the level of detergent pollution in the water, the more severe the death of the aquatic biota, and vice versa, the lower the level of pollution, the better the life of the aquatic biota there. Pollution is also one of the disruptors in the respiration process in the ecosystem in it so that the ecosystem will be disturbed by the amount of pollution from tourists and the domestic waste they bring. This research was conducted qualitatively using observational and experimental methods to measure detergent levels in the waters. The parameters examined were water temperature, pH, chemical content, and the fish present in the Cirahab waters. The results showed very high detergent concentrations, with plastic waste, bottles, and food waste from visitors scattered throughout the Cirahab waters. This disrupted the aquatic ecosystem and threatened the survival of aquatic life, including fish. Fish experienced respiratory problems, including gill damage, and even mass mortality in the Cirahab waters.